The Effect of Novel Attributes on Product Evaluation - Mukherjee, Ashesh; Hoyer, Wayne D. (Journal of Consumer Research, 2001)
Abstract Many technological innovations introduce attributes that are novel or completely unknown to a large number of consumers. For example, recently introduced attributes such as GPS in cars or I-Link in computers are likely to have been novel to many consumers. Past research suggests that the addition of novel attributes is likely to improve product evaluation and sales, since consumers interpret these attributes as additional benefits provided by the manufacturer. However, this article demonstrates that the positive effect of novel attributes holds only in the case of low-complexity products. In the case of high-complexity products, the addition of novel attributes can actually reduce product evaluation because of negative learning-cost inferences about these attributes. Further, the positive and negative effects of novel attributes on product evaluation are accentuated by external search for information when the information discovered through search is ambiguous in nature. Finally, it is shown that the negative effect of novel attributes on the evaluation of high-complexity products can persist even after consumers are given explicit information about the benefits of novel attributes. A key marketing implication of these findings is that novel attributes may contribute to technophobia, or consumer resistance toward technological innovation.